Association between psychological capital and depressive symptoms during COVID-19: The mediating role of perceived social support and the moderating effect of employment pressure - Huang, Yalian; Lin, Xin; Yang, Jian; Bai, Hefei; Tang, Ping; Yuan, Guangzhe Frank (Frontiers in Public Health, 2023)
Prior research has demonstrated that both psychological capital and perceived social support are related to the severity of depression. Yet no study explored the direction of associations between these factors. This study aimed to explore the association between psychological capital, perceived social support, employment pressure, and depressive symptoms during COVID-19. A cross-sectional design was employed in a sample of 708 Chinese senior medical students who were asked to complete an online questionnaire survey. Results indicated that psychological capital and perceived social support negatively predicted participants’ depressive symptoms. Employment pressure significantly moderated the relationship between psychological capital and depressive symptoms. The current study highlights that it is of great significance to address Chinese medical students' employment pressure and improve their mental health during the COVID-19 epidemic.